2018
DOI: 10.1186/s13568-018-0703-3
|View full text |Cite
|
Sign up to set email alerts
|

Light-harvesting protein Lhcx3 is essential for high light acclimation of Phaeodactylum tricornutum

Abstract: The light-harvesting protein complexes (Lhc) play key roles in the processes of light absorption and protection in diatoms. However, different Lhc protein carries out distinct function in photosynthesis. For now, roles of many Lhc proteins in light acclimation are largely unknown. Here, function of Lhcx3 in marine diatom Phaeodactylum tricornutum was examined by using reverse genetic technologies. The overexpression of Lhcx3 led to increased diadinoxanthin + diatoxanthin content and elevated non-photochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…When cells were exposed to high light, NPQ was activated to convert excess light energy into heat energy ( Nymark et al, 2009 ). In diatoms, Ddx cycle plays a critical role in NPQ, which protects cell from high-light damage ( Hao et al, 2018 ). Under high light, the contents of Ddx and Fx were lower than low light ( Conceicao et al, 2020 ), which due to the upregulation of VDE promoted the conversion of Ddx to Dtx and violaxanthin to zeaxanthin, leading to the decline of Fx ( Nymark et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…When cells were exposed to high light, NPQ was activated to convert excess light energy into heat energy ( Nymark et al, 2009 ). In diatoms, Ddx cycle plays a critical role in NPQ, which protects cell from high-light damage ( Hao et al, 2018 ). Under high light, the contents of Ddx and Fx were lower than low light ( Conceicao et al, 2020 ), which due to the upregulation of VDE promoted the conversion of Ddx to Dtx and violaxanthin to zeaxanthin, leading to the decline of Fx ( Nymark et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“… 211 , 212 Bitto et al also found that, in some cases, genistein aglycone also showed a positive outcome for methylprednisolone‐induced necrotic deterioration of the femoral head. 209 Vinpocetine, a natural compound extracted from the leaves of Phyllostachys pubescens , 213 has also shown a protective role in ON of the femoral head in rat models. 214 However, the protective effect of natural compounds on ON has not been tested in clinical human studies and needs to be further studied in ON patients.…”
Section: Glucocorticoid‐induced Osteonecrosis Animal Modelsmentioning
confidence: 99%
“…To understand how diatoms respond to high-light stress, we initially aimed to identify the relevant LHCX family members involved in acclimation to high light in P. tricornutum . Among its four LHCX isoforms, although LHCX2 and LHCX3 are upregulated under high light 39 , 59 , P. tricornutum cells harboring a mutation in LHCX2 or silenced LHCX3 expression exhibit only modestly lower NPQ than wild-type cells 20 , 60 . To investigate whether LHCX2 and LHCX3 can functionally compensate each other, we generated and phenotyped their single and double mutants (see Supplementary Data 1 for all primers) under light stress.…”
Section: Resultsmentioning
confidence: 99%